Motivation Of Ethical Sharia Property Investment for The Millennial And Generation Z - Sapitri, Dianing (ITB AAS INDONESIA Surakarta, 2024)
Generation Millennials and Gen-Z mostly feel the development economy is Sharia moment now and for the future. Business property in Indonesia is increasing increase with requests for property residential green living. Investment property Sharia ethical is one choice for future business. Objective This research is to analyze motivation investment property Sharia necessary ethics now and in the future, and education understanding Islamic Sharia in support economy people following the teachings of the Qur'an and hadith. The study uses method qualitative descriptive through analysis deep from various relevant literature. Research results show that; 1) Generation Millennials and Gen-Z have already voted for property sharia although not as much non-real investment moment this. 2) Digital literacy and da'wah for education must be broad and creative to add insight and confidence. 3) Profits obtained that is; spared from usury, appropriate with principles Sharia with Islamic ethics, investment sustainable, profitable results competitive, and contributing to welfare and environment public. 4) Challenge more digital innovation lively the application or investment platform property sharia for convenience communication and transactions. A must opportunity supported by regulations government and institutions finances for improvement and development economy sharia globally, for blessings in this world and the hereafter.